A large-scale, geographical approach to using group concept mapping for planning: The Teen Opinions Count (TOC) project. (June 2022) - Rosas, Scott R.; Smith, Corey; Eenigenburg, Avery; BaileyShea, Chelsea; Jerome, Kathleen; Millane, Maureen
Abstract: The use of group concept mapping (GCM) for large-scale, multi-site planning has been limited. The Teens Opinions Count (TOC) project utilized the group concept mapping methodology to develop a framework for after school time program development for teens in 16 counties in the Southeast Michigan and Western New York regions. This extensive planning effort demonstrated a large-scale, geographical approach to the implementation of GCM, where multiple sites (in this case counties) simultaneously engaged in independent processes on the same topic, with the purpose of producing separate locale-specific conceptualizations. TOC was the largest GCM project ever conducted in terms of the number of participants and volume of data submitted. This report details GCM recruitment, data collection, data compilation, and analysis of ideas from over 20, 000 teens and 2, 000 adults. Although implementation was conducted at the county level, many of the separate county-level GCM processes were larger than what is typically encountered in the literature. Operationalizing GCM at such a scale required significant planning, design, communication, and data management solutions. The extensive data collection effort required the need for creative and innovative procedures to engage teens and process the sheer volume of data. The lessons learned are discussed and suggestions for future applications offered. Highlights: Group concept mapping was used to facilitate large scale planning for after school time. Multi-step process for teens and adults to identify, shape, and elevate after school ideas. Teen Opinions Count reached over 20, 000 teens and 2000 adults in 16 counties across MI and NY. Implemented at this scale, one needs to consider recruitment and data collection activities for GCM. More concrete clusters of ideas had consistently lower bridging values; more ambiguous clusters had consistently higher values.